Correlation of Bone Metabolism with Serum Pain Mediators and Inflammatory Cytokines in Knee Osteoarthritis and Their Role in Predicting Suboptimal Rehabilitation Outcomes - Tao, Yan; Cai, Nan; Zhang, Juxia; Zhao, Yaoping; Zhou, Yan; Liu, Pengfei (Journal of Medical Biochemistry, 2025)
Objective: The present study was designed to investigate how bone metabolism markers—specifically Procollagen Type I N-Terminal Propeptide (PINP) and C-Telopeptide of Type I Collagen (CTX)—correlate with serum pain mediators (Prostaglandin E₂ [PGE₂], Norepinephrine [NE], Substance P [SP]) and inflammatory cytokines (Interleukin-1β [IL-1β], Interleukin-6 [IL-6], Tumor Necrosis Factor-α [TNF-α]) in individuals with knee osteoarthritis (KOA). A further aim was to develop a multi-biomarker predictive model for identifying patients at risk of suboptimal rehabilitation outcomes to guide targeted clinical management.Methods: In this prospective cohort study, 184 KOA patients and an equal number of matched healthy controls were enrolled between January 2023 and May 2024. Using baseline serum, biomarker levels were assessed; Enzyme-Linked Immunosorbent Assay (ELISA) was employed for all analytes except SP, which was determined by radioimmunoassay. The primary endpoint, suboptimal rehabilitation outcome, was determined as either a